Lithic Technological Organization and Hafting in Early Villages. Issue 4 (October 2019) - Quinn, Colin P.; Goodale, Nathan; Andrefsky, William; Kuijt, Ian; Finlayson, Bill
Abstract : Hafting is an important part of lithic technology that can increase our understanding of socioeconomic behavior in the past. In this article, we develop a holistic approach to studying hafting by using the concept of curation within a broader assessment of lithic technological organization in early villages. Early villages were loci of socioeconomic transformation as part of the shift from mobile foraging to more sedentary cultivation lifeways. We suggest that an examination of hafting can provide new insights into how early villagers negotiated technological requirements, economic decision making, and social interactions in these novel contexts. As a case study, we develop a curation index and apply it to an archaeological context of hafted and unhafted pointed tools from the early Neolithic village of Dhra', Jordan. This curation index allows for a discussion of the technological, economic, and social dimensions of hafting strategies at Dhra'. The presence of multiple hafting traditions within early Neolithic villages of Southwest Asia is evidence of persistent social segmentation despite food storage and ritual practices that emphasized communal integration. Through the lens of lithic technological organization, we demonstrate that hafting and curation patterns can increase our understanding of technological, economic, and social strategies in early villages. Abstract : El enmangue es una parte importante de la tecnología lítica que puede aumentar nuestra comprensión del comportamiento socioeconómico en el pasado. En este trabajo, desarrollamos un enfoque holístico para el estudio de la utilización del concepto de curación dentro de una evaluación más amplia de la organización tecnológica lítica en las aldeas primitivas. Las aldeas tempranas fueron lugares de transformación socioeconómica como parte del cambio de alimentación móvil a formas de vida de cultivos más sedentarios. Sugerimos que la examinación de los acontecimientos del enmangue puede proporcionar nuevos conocimientos sobre cómo los aldeanos negociaron los requisitos para la tecnología, la toma de decisiones económicas y las interacciones sociales en estos nuevos contextos. Como estudio de caso, desarrollamos un índice de curación y lo aplicamos a un contexto arqueológico de las herramientas puntiagudas y sin puntillas de la antigua aldea neolítica de Dhra', Jordania. Este índice de curación permite una discusión de las dimensiones tecnológicas, económicas y sociales de las estrategias de desarrollo en Dhra'. La presencia de múltiples tradiciones de hospedaje en las aldeas neolíticas tempranas del sudoeste de Asia es evidencia de una persistente segmentación social a pesar del almacenamiento de alimentos y las prácticas rituales que enfatizan la integración comunitaria. A través de la lente de la organización tecnológica lítica, demostramos que los patrones de cuidado y curación pueden proporcionar una mejor comprensión de las estrategias tecnológicas, económicas y sociales en las aldeas primitivas.